Is Hezekiah a Success or a Failure?: The Literary Function of Isaiah's Prediction at the End of the Royal Narratives in the Book of Isaiah - Jang, Sehoon (Journal for the study of the Old Testament, 2017)
Recent studies on both the redactional and literary unity of Isaiah have emphasized the pivotal role of Isaiah 36-39 as a transitional bridge between the two major parts of the book of Isaiah. More specifically, a growing number of commentators have understood that Hezekiah is cast as an ideal role model and remains exemplary even in Isaiah 39. However, this interpretation of Hezekiah as an idealized king is an oversimplification and does not recognize the complexity of the character of Hezekiah portrayed in these chapters. The purpose of this article is to propose a synchronic reading of how Isaiah's prediction at the end of the royal narratives in the book of Isaiah plays a key role in providing a coherent evaluation of Hezekiah as a blemished monarch who used to be a success but has become a failure.